Effect of ractopamine on growth in cattle - Walker, Dillon Kyle (Kansas State University, 2008)
Ractopamine is a repartitioning agent that can increase muscle growth and has led to our interest in determining the mechanisms involved in enhancing muscle growth. Therefore, three studies were conducted to determine the impact of ractopamine on growth in cattle. The first experiment evaluated the impact of increasing metabolizable protein supply to finishing heifers fed ractopamine. Three different diets were fed to increase the amount of metabolizable protein reaching the small intestine, and the diets contained urea, solvent soybean meal, or expeller soybean meal as the primary supplemental protein source. From this study it was determined that increasing metabolizable protein supply above that present in typical feedlot diets containing urea and steam-flaked corn is not necessary to improve responsiveness to ractopamine. The second experiment evaluated the effect of feeding ractopamine to growing Holstein steers implanted with trenbolone acetate/estradiol. Half of the steers were implanted 28 days prior to all steers receiving ractopamine for the final 28 days; this model represents an intense implant program. The mode of action of the ractopamine and of steroidal implants was different based on their different effects on serum insulin-like growth factor (IGF)-I and longissimus expression of IGF-I mRNA. Additionally, administering a combination of the two growth promotants, based on nitrogen retention, yields a less than additive response using our model of growing Holstein steers. The third study was conducted to evaluate the differential response to ractopamine of implanted, finishing steers and heifers. Treatments were steer vs. heifer and 0 vs. 200 mg/d ractopamine fed for the final 28 days. This study attempted to address some questions generated from the previous study, which were how serum and local tissue production of IGF-I are affected by ractopamine. Ractopamine had different effects on serum IGF-I between steers and heifers and numerically increased IGF-I mRNA abundance in longissimus and biceps femoris muscles. Additionally, ractopamine impacted protein turnover differently in different muscles and changed myosin heavy chain IIA expression. The effect of ractopamine on IGF-I warrants more research. These experiments aid in our understanding of the mode of action of ractopamine in cattle.
Keywords: Ractopamine; Cattle; Agriculture, Animal Culture and Nutrition (0475)